TINJAUAN YURIDIS PENEGAKAN HUKUM TERHADAP PENCEMARAN LINGKUNGAN AKIBAT KEGIATAN PENAMBANGAN BATUBARA DI KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA - Mohamad Fadli (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractEnvironmental law in general to solve environmental problems especially caused by human activities. Environmental problems for humans can be seen in terms of environmental quality decline.The presence of massive coal mining activities in Tenggarong Seberang sub-district of Kutai Kartanegara Regency has caused damage to the environment in the region. Surely this is very inconvenient for the life of the surrounding community. One of the efforts to reduce the level of environmental pollution as a result of coal mining activities is through strict environmental monitoring and law enforcement against companies that pollute the environment.There are 3 (three) things studied in this research are: 1) How many cases and types of environmental imaging conducted by coal mining companies in Tenggarong Seberang Sub-district Kutai Kartanegara Regency during the last 5 years (2011-2015)? ; 2) what are the forms given to companies for environmentalists in Tenggarong Seberang sub-district of Kutai Kartanegara Regency for the last 5 years (2011-2015)? and 3) What are the procedures for monitoring and sanctioning the companies that pollute the environment? The method used in this research is the normative method and sociological method (empirical).Based on the results of research that has been done, the number of environmental dispute cases related to coal mining activities in Tenggarong Seberang District Kutai Kartanegara Regency during the period 2011-2015 as many as 52 cases and environmental components which are the activities of air (17 cases), soil (36 cases), air / vibration (3 cases) and cumulative (1 case). The number of companies reported as many as 27 companies and cases that have been completed as many as 50 cases while 2 cases are still in the process of completion. The highest number of cases in 2012 is as many as 14 cases while the number of cases occurred in the year 2013 as many as 6 cases. All cases.Implementation of sanctions to coal mining company in Tenggarong Seberang Sub-district Kutai Kartanegara Regency for 2011-2015 period as many as 8 companies with billing forms namely written warning (3 companies), government coercion (3 companies) and freezing of environmental permit (2 companies), while the word replacement termination no company got the order. The amounts divided in 2011 and 2012 are 3 companies each and in 2013 as 2 temporary companies in the last 2 years (2014-2015) there is no company. Forms of sanction given to companies that conduct the environment (pollution and / or environmental damage). Not all cases are sick or only 15.38% of cases of pollution and / or environmental damage are given sanctions.The Regional Environment Agency (BLHD) of Kutai Kartanegara Regency already has Standard Operating (SOP) related to environmental law enforcement in Kutai Kartanegara Regency, namely: 1) SOP of Administrative Sanction Implementation in the field of Environmental Protection and Management and SOP of Environmental Law Enforcement. Nevertheless BLHD Kutai Kartanegara does not yet have SOP related to law enforcement related to. The main obstacle of BLHD Kutai Kartanegara in conducting supervision and enforcement of environmental law is the number of personnel (PPNS and PPLHD) and limited operational fund.